Transiting images - Salvatori, Maristela (PORTO ARTE: Revista de Artes Visuais, 2013)
The text partially presents aspects of the development of the project entitled Transiting images, carried out in Université Laval, Canada. The research aimed on creating a series of urban landscapes through the use of different visual resources such as printmaking, monotype, photography and digital printing, and focused on contemporary possibilities of expression of the multiple.